2003
DOI: 10.1073/pnas.252763199
|View full text |Cite
|
Sign up to set email alerts
|

Domestication quantitative trait loci inTriticum dicoccoides, the progenitor of wheat

Abstract: Wild emmer wheat, Triticum dicoccoides, is the progenitor of modern tetraploid and hexaploid cultivated wheats. Our objective was to map domestication-related quantitative trait loci (QTL) in T. dicoccoides. The studied traits include brittle rachis, heading date, plant height, grain size, yield, and yield components. Our mapping population was derived from a cross between T. dicoccoides and Triticum durum. Approximately 70 domestication QTL effects were detected, nonrandomly distributed among and along chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
223
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(253 citation statements)
references
References 53 publications
29
223
0
1
Order By: Relevance
“…Comparative analysis with the known major QTL for yield in wheat: A survey of the literature reporting QTL for GY and related agronomic traits in both tetraploid and hexaploid wheat (Li et al 2002;Peng et al 2003;Elouafi and Nachit 2004;Huang et al 2004Huang et al , 2006McCartney et al 2005;Quarrie et al 2005Quarrie et al , 2007Marza et al 2006;Narasimhamoorthy et al 2006;Kuchel et al 2007;Kumar et al 2007;Ma et al 2007) revealed rather different scenarios for the two major GY QTL identified in our study. Our comparative analysis was carried out by relating the (LOD À 1) supporting interval of the QTL to the Ta-SSR-2004 consensus map (Somers et al 2004).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Comparative analysis with the known major QTL for yield in wheat: A survey of the literature reporting QTL for GY and related agronomic traits in both tetraploid and hexaploid wheat (Li et al 2002;Peng et al 2003;Elouafi and Nachit 2004;Huang et al 2004Huang et al , 2006McCartney et al 2005;Quarrie et al 2005Quarrie et al , 2007Marza et al 2006;Narasimhamoorthy et al 2006;Kuchel et al 2007;Kumar et al 2007;Ma et al 2007) revealed rather different scenarios for the two major GY QTL identified in our study. Our comparative analysis was carried out by relating the (LOD À 1) supporting interval of the QTL to the Ta-SSR-2004 consensus map (Somers et al 2004).…”
Section: Discussionmentioning
confidence: 55%
“…2BL (Bö rner et al 2002;Marza et al 2006), and QTL for GY, kernel weight, and number of kernels per spike have been reported on chr. 2AL (Bö rner et al 2002;Peng et al 2003;Huang et al 2004;McCartney et al 2005), but not in the distal region. Conversely, major QTL for GY have been identified in two different genetic backgrounds (Bö rner et al 2002;Campbell et al 2003) on the short distal regions of chr.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another possible explanation for the LD block on 5A would be the loss of variability during domestication, in which case the LD block should exist in other wheat classes as well. An important domestication-related QTL that affected grain weight, grain number per spike, plant height, heading date, and yield per plant has been detected in this region (Peng et al 2003).…”
Section: 46)mentioning
confidence: 95%
“…dicoccoides) should also be useful, allowing detection of favourable alleles from both the tetraploid and diploid exotic parents. Wild emmer proved already as a donor of useful genetic variation for important agronomic traits in tetra-and hexaploid wheat, contributing to powdery mildew resistance, rust resistance, reduced plant height, early heading, increased number of spikes per plant, higher spike weight per plant, increased kernels per spikelet and higher yield (Peng et al 1999(Peng et al , 2003Rong et al 2000). Wild emmer also proved to possess genes improving grain quality in wheat.…”
Section: Introductionmentioning
confidence: 99%